Non-alcoholic fatty liver disease - Powell, Elizabeth E; Wong, Vincent Wai-Sun; Rinella, Mary (The Lancet (British edition), 2021)
Non-alcoholic fatty liver disease (NAFLD) has a global prevalence of 25% and is a leading cause of cirrhosis and hepatocellular carcinoma. NAFLD encompasses a disease continuum from steatosis with or without mild inflammation (non-alcoholic fatty liver), to non-alcoholic steatohepatitis (NASH), which is characterised by necroinflammation and faster fibrosis progression than non-alcoholic fatty liver. NAFLD has a bidirectional association with components of the metabolic syndrome, and type 2 diabetes increases the risk of cirrhosis and related complications. Although the leading causes of death in people with NAFLD are cardiovascular disease and extrahepatic malignancy, advanced liver fibrosis is a key prognostic marker for liver-related outcomes and overall mortality, and can be assessed with combinations of non-invasive tests. Patients with cirrhosis should be screened for hepatocellular carcinoma and oesophageal varices. There is currently no approved therapy for NAFLD, although several drugs are in advanced stages of development. Because of the complex pathophysiology and substantial heterogeneity of disease phenotypes, combination treatment is likely to be required for many patients with NAFLD. Healthy lifestyle and weight reduction remain crucial to the prevention and treatment of NAFLD.